Genetic relatedness of Legionella longbeachae isolates from human and environmental sources in Australia. - Lanser, J A (1990)
The genetic relatedness of Legionella longbeachae isolated in Australia since 1987 was investigated by restriction fragment length polymorphism (RFLP) analysis and allozyme electrophoresis. Three radiolabeled probes were used in Southern hybridizations for the RFLP studies. They were Escherichia coli 16S and 23S rRNA and cloned fragments of L. longbeachae selected empirically from genomal banks in lambda and a cosmid. The legionellae included in the study comprised 11 Legionella longbeachae serogroup 1 organisms isolated from humans, 28 L. longbeachae serogroup 1 isolates from environmental sources, and 3 L. longbeachae serogroup 2 environmental isolates. These were compared with the American Type Culture Collection reference strains of both serogroups and some other related Legionella species. Results of allozyme and RFLP analysis showed that all the isolates from humans and all but three of the environmental L. longbeachae serogroup 1 isolates were closely related. They were also closely related to L. longbeachae serogroup 1 ATCC 33462. There was wider variation among the three L. longbeachae serogroup 2 environmental isolates. One of these was closely related to L. longbeachae serogroup 2 ATCC 33484. RFLP studies with the rRNA probe provided the most discrimination among isolates but did not distinguish between the two serogroups.